Analisis Kesiapan Pengguna di Indonesia dalam Adopsi Teknologi Blockchain Pada Platform Pertukaran Kripto Menggunakan TRI - Sri Putri Nurjanah; Asti Herliana (Jurnal Teknologi Informasi dan Multimedia, 2026)
The use of blockchain technology on cryptocurrency exchange platforms in Indonesia has experi-enced notable growth, yet challenges persist concerning user preparedness and preferences be-tween domestic and international platforms. This research seeks to explore the factors influencing users’ selection of crypto platforms and to evaluate the technological readiness of Indonesian us-ers by integrating the Technology Readiness Index (TRI) with an information technology adop-tion framework. The study employed purposive sampling to gather data from 156 active crypto platform users. Quantitative data analysis was performed using PLS-SEM through SmartPLS version 4.0. Findings indicate that the majority of respondents are young adults aged 17 to 25, predominantly male, and show a preference for international platforms due to their innovative capabilities, greater liquidity, and lower transaction fees. Nonetheless, local platforms remain attractive because of easier accessibility and enhanced regulatory backing. Structural model re-sults demonstrate that optimism, innovativeness, and insecurity significantly influence user readiness, whereas discomfort does not have a meaningful impact. Moreover, user readiness stands out as a critical factor strongly facilitating blockchain technology adoption on crypto ex-changes. This study validates the combined application of the TRI and IT adoption models as ef-fective tools for pinpointing key determinants of blockchain adoption readiness, offering strategic insights for developers of local platforms and serving as a foundation for future research on blockchain implementation in Indonesia.